Powering Predictions for United States Coast Guard Proposed Icebreaker Design Represented by Model 5169. - Day, W. G., Jr (1969)
The United States Coast Guard established a model test program at this Center to evaluate an altered hull form for a new icebreaker design. Bare hull resistance tests, bossing wake surveys, and flow observations have been completed and show the bossing design to be acceptable. This being the case, the appendaged EHP and SHP tests and the towing tests were conducted. Following these tests with the original propellers the centerline propeller was repitched and the tests were repeated at two displacements. The results of these tests are reported.